Erythrodiol, an Olive Oil Constituent, Increases the Half-Life of ABCA1 and Enhances Cholesterol Efflux from THP-1-Derived Macrophages - Wang, Limei; Wesemann, Sarah; Krenn, Liselotte; Ladurner, Angela; Heiss, Elke H.; Dirsch, Verena M.; Atanasov, Atanas G. (Frontiers in Pharmacology, 2017)
Cholesterol efflux (ChE) from macrophages is an initial step of reverse cholesterol transport (RCT). The ATP-binding cassette transporter A1 (ABCA1) is a key transporter for ChE and its increased expression is regarded to attenuate atherosclerosis. Thus, the identification and characterization of molecules raising ABCA1 and thereby stimulating ChE is of pharmacological relevance. In this study, we tested dietary compounds from olive oil for their capacity of enhancing cellular ABCA1 protein level. We identified erythrodiol (Olean-12-ene-3β,28-diol) as an ABCA1 stabilizer and revealed its positive influence on ChE in THP-1-derived human macrophages. Among the 9 tested compounds from olive oil, erythrodiol was the sole compound raising ABCA1 protein level (at 10 μM). None of the tested compounds impaired viability of THP-1 macrophages from 5 to 20 μM as determined by resazurin conversion. Western blot analyses of key membrane transporters contributing to ChE showed that the protein level of ABCG1 and scavenger receptor class B member 1 (SR-B1) remain unaffected by erythrodiol. Besides, erythrodiol (10 µM) did not influence the mRNA level of ABCA1, ABCG1 and SR-B1, as determined by quantitative reverse transcription PCR, but significantly inhibited the degradation of ABCA1 as evident by an increased half-life of the protein in the presence of cycloheximide, an inhibitor of de novo protein synthesis. Therefore, erythrodiol promotes ChE from THP-1-derived human macrophages by stabilizing the ABCA1 protein. This bioactivity makes erythrodiol a good candidate to be further explored for therapeutic or preventive application in the context of atherosclerosis.